2008
DOI: 10.2174/157341308783591799
|View full text |Cite
|
Sign up to set email alerts
|

Developing a New Generation of Bone Cements With Nanotechnology

Abstract: Around 500,000 people have total joint (including hip and knee) replacement surgeries each year. However, current joint implants last only 10 to 15 years before failing. Undoubtly because of this, many patients have to go through a revision surgery due to the failure of bone implants. The main reason for implant failure is aseptic loosening of the implant from juxtaposed bone. In this light, polymethyl methacrylate (PMMA) has been used widely in orthopedics to improve the bonding between the implant and bone. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 70 publications
2
24
0
Order By: Relevance
“…Results of the present study demonstrated that osteoblast adhesion was higher on PMMA cements with either nanophase MgO or conventional and nanophase BaSO 4 than pure PMMA cement. Results of improved osteoblast adhesion on PMMA with nanometer compared to micron particles of MgO confi rms that of other studies which have shown greater osteoblast functions on nanometer compared with conventional ceramics, metals, polymers, and composites (Liu-Synder and Webster 2007). However, future investigations will be needed to elucidate why greater osteoblast adhesion was not observed on nanometer compared with micron BaSO 4 added to PMMA.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…Results of the present study demonstrated that osteoblast adhesion was higher on PMMA cements with either nanophase MgO or conventional and nanophase BaSO 4 than pure PMMA cement. Results of improved osteoblast adhesion on PMMA with nanometer compared to micron particles of MgO confi rms that of other studies which have shown greater osteoblast functions on nanometer compared with conventional ceramics, metals, polymers, and composites (Liu-Synder and Webster 2007). However, future investigations will be needed to elucidate why greater osteoblast adhesion was not observed on nanometer compared with micron BaSO 4 added to PMMA.…”
Section: Discussionsupporting
confidence: 75%
“…BaSO 4 micron agglomerates serve as initiation sites for fatigue cracks. It has also been found that PMMA wear particles that contain micron-sized BaSO 4 and ZrO 2 particles cause more bone resorption than pure PMMA wear particles; this has lead to increased osteolysis when micron-sized BaSO 4 and ZrO 2 particles are used in PMMA (Liu-Synder and Webster 2007). In addition, although more testing is needed, recent studies have demonstrated less adverse reactions of ceramic nanoparticulate compared to micron wear debris (Liu-Synder and Webster 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations